2021
DOI: 10.1166/jnn.2021.18637
|View full text |Cite
|
Sign up to set email alerts
|

Investigate the Effect of miR-22 on the Apoptosis of Coronary Heart Disease Cells Through the Wnt-1 Pathway Based on Nano-Silica-Induced Rat Models

Abstract: In this paper, by examining the toxicity of nano-silica to coronary heart disease cells, we explored the apoptosis of rat myocardial cells induced by nano-silica, and explored the effect of apoptosis on cells during the process of myocardial cytotoxicity induced by nano-silica. This article selects rat cardiomyocytes as the research object and conducts a group control experiment. A control group is set up with cells that are not stained with nano-silica. Different concentrations of nanosilica suspensions are … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(1 citation statement)
references
References 17 publications
0
1
0
Order By: Relevance
“…Researchers have found that many signaling pathways are involved in the biological processes of apoptosis and autophagy, such as the Wnt-1, PI3K/Akt/mTOR, Nrf2/ARE and JAK/STAT3 signaling pathway (Gureev et al, 2020;Jin et al, 2020;Ning et al, 2020;Wei et al, 2021;Zhao et al, 2020). Among these, the PI3K/Akt/mTOR and Nrf2/ARE signaling pathways have attracted great attention.…”
Section: Discussionmentioning
confidence: 99%
“…Researchers have found that many signaling pathways are involved in the biological processes of apoptosis and autophagy, such as the Wnt-1, PI3K/Akt/mTOR, Nrf2/ARE and JAK/STAT3 signaling pathway (Gureev et al, 2020;Jin et al, 2020;Ning et al, 2020;Wei et al, 2021;Zhao et al, 2020). Among these, the PI3K/Akt/mTOR and Nrf2/ARE signaling pathways have attracted great attention.…”
Section: Discussionmentioning
confidence: 99%